Sex-based differences in outcomes, 30-day readmissions, and costs following catheter ablation of atrial fibrillation: the United States Nationwide Readmissions Database 2010–14. (29th March 2019) - Cheung, Jim W; Cheng, Edward P; Wu, , Xian; Yeo, Ilhwan; Christos, Paul J; Kamel, Hooman; Markowitz, Steven M; Liu, Christopher F; Thomas, George; Ip, James E; Lerman, Bruce B; Kim, Luke K
Abstract: Aims: Although catheter ablation has emerged as an important therapy for patients with symptomatic atrial fibrillation (AF), there are limited data on sex-based differences in outcomes. We sought to compare in-hospital outcomes and 30-day readmissions of women and men undergoing AF ablation. Methods and results: Using the United States Nationwide Readmissions Database, we analysed patients undergoing AF ablation between 2010 and 2014. Based on ICD-9-CM codes, we identified co-morbidities and outcomes. Multivariable logistic regression and inverse probability-weighting analysis were performed to assess female sex as a predictor of endpoints. Of 54 597 study patients, 20 623 (37.7%) were female. After adjustment for age, co-morbidities, and hospital factors, women had higher rates of any complication [adjusted odds ratio (aOR) 1.39; P < 0.0001], cardiac perforation (aOR 1.39; P = 0.006), and bleeding/vascular complications (aOR 1.49; P < 0.0001). Thirty-day all-cause readmission rates were higher for women compared to men (13.4% vs. 9.4%; P < 0.0001). Female sex was independently associated with readmission for AF/atrial tachycardia (aOR 1.48; P < 0.0001), cardiac causes (aOR 1.40; P < 0.0001), and all causes (aOR 1.25; P < 0.0001). Similar findings were confirmed with inverse probability-weighting analysis. Despite increased complications and readmissions, total costs for AF ablation were lower for women than men due to decreased resource utilization. Conclusions: Independent of age, co-morbidities, and hospital factors, women have higher rates of complications and readmissions following AF ablation. Sex-based differences and disparities in the management of AF need to be explored to address these gaps in outcomes.